Philosophy of education: â€œTut Wuri Handayaniâ€ as the spirit of governance process in Indonesia's educational organization - Hermawan, Agus; Tan, Emily B. (International Journal of Humanities and Innovation (IJHI), 2021)
â€˜Tut Wuri Handayaniâ€™ is the slogan of the National Education of Indonesia, written in Sanskrit. It is a philosophy of education that Ki Hajar Dewantara originally promoted. Practically, it is an accumulation of educational processes that prioritize the transformation of good character and knowledge through a governance organization that is instigated by educational leadership. In this regard, the paper utilizes the literature review method to get information from researchers published in refereed journals regarding process governance, model of governance organization in school and synthesizes the information to show how the school leaders can promote â€œTut Wuri Handayaniâ€ in order that it can be integrated into the school governance. This paper invites researchers to apply qualitative research designs to explore the possibility of implementing the Philosophy Education: â€œTut Wuri Handayaniâ€ in the governance organization of Schools in Indonesia. Indonesia's educational system has experimented with several forms of leadership. The paper discusses the necessity of promoting the Indonesian philosophy of education, â€˜Tut Wuri Handayani,' to preserve its worth as a guide for all school leaders and instructors to maintain a positive attitude and behavior to achieve educational goals. School leaders and instructors are encouraged to use this Indonesian Philosophy of Education to ensure that children always receive a decent education and in all places. The authors also recommend that module and curriculum creators collaborate with learning facilitators to integrate the Philosophy of Education: â€˜Tut Wuri Handayani' as one of the school governance principles and values. In addition, this research suggests that future researchers use qualitative research designs to investigate the influence of the implementation of â€˜Tut Wuir Handayani' on students, school leaders, teachers, and other stakeholders in a sample of Indonesian schools.